2013
DOI: 10.1371/journal.pone.0053248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Context on Visuomotor Interference Depends on the Perspective of Observed Actions

Abstract: Visuomotor interference occurs when the execution of an action is facilitated by the concurrent observation of the same action and hindered by the concurrent observation of a different action. There is evidence that visuomotor interference can be modulated top-down by higher cognitive functions, depending on whether own performed actions or observed actions are selectively attended. Here, we studied whether these effects of cognitive context on visuomotor interference are also dependent on the point-of-view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…This interaction arose from a much larger congruency effect for images presented in the egocentric perspective (congruent: 646 ± 159 msec, incongruent: 726 ± 197 msec) compared with images presented in the allocentric perspective (congruent: 661 ± 172 msec, incongruent: 701 ± 184 msec). These results replicate those reported in a recent study in which we examined the effects of perspective and context on visuomotor interference (Bortoletto et al, 2013) and are consistent with previous studies showing that action images presented from an egocentric perspective trigger stronger visuomotor interference than images from an allocentric perspective (Bruzzo, Borghi, & Ghirlanda, 2008;Jackson, Meltzoff, & Decety, 2006). Error rates on the task were low and did not differ significantly between conditions, suggesting that participants performed the task well and according to instructions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This interaction arose from a much larger congruency effect for images presented in the egocentric perspective (congruent: 646 ± 159 msec, incongruent: 726 ± 197 msec) compared with images presented in the allocentric perspective (congruent: 661 ± 172 msec, incongruent: 701 ± 184 msec). These results replicate those reported in a recent study in which we examined the effects of perspective and context on visuomotor interference (Bortoletto et al, 2013) and are consistent with previous studies showing that action images presented from an egocentric perspective trigger stronger visuomotor interference than images from an allocentric perspective (Bruzzo, Borghi, & Ghirlanda, 2008;Jackson, Meltzoff, & Decety, 2006). Error rates on the task were low and did not differ significantly between conditions, suggesting that participants performed the task well and according to instructions.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, our Experiment 1 suggests that, when observed actions, as the go cue, are seen from an allocentric perspective, the congruency effect is reversed relative to when actions are observed from an egocentric perspective (Press et al, 2010). In a purely behavioral study, we recently reported that the effect of cognitive context on visuomotor interference is indeed perspective-dependent, that is, visuomotor interference in the action context is stronger for gesture images from an egocentric perspective than for those from an allocentric perspective (Bortoletto, Mattingley, & Cunnington, 2013). Hand images in the egocentric perspective better match the representation of the action outcome that is created at the time of movement initiation (Kilner, Friston, & Frith, 2007;Hommel, Müsseler, Aschersleben, & Prinz, 2001) and may therefore trigger different matching processes between predicted and observed action outcomes (Bortoletto et al, 2013).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Typically, correlational studies investigating perspectives as an indication of self-other differentiation have shown that egocentric stimuli induce greater neurophysiological and behavioural responses compared to allocentric stimuli. For example, it has been observed: greater cortical activity in the sensorymotor cortex (Jackson et al, 2006), greater visuomotor interference (Bortoletto et al, 2013;Vogt et al, 2003) and larger motor-evoked potentials (MEPs) as induced by transcranial magnetic stimulation (TMS) during the observation of egocentric movements (Maeda et al, 2002). However, these correlational reports have not always been consistent; Alaerts and colleagues (2009) reported that MEPs are not necessarily larger for egocentric movements per se; rather, MEP's are larger for an egocentric right hand and for an allocentric left hand.…”
Section: Introductionmentioning
confidence: 99%